Simulation of power transmission from solar cells into A single-phase grid system using eleven levels of inverters - Chaithanakulwat, Arckarakit (International Review on Modeling and Simulations, 2020)
This paper offers a way to simulate the transmission of electric power from solar cells using the inverter level 11 to the grid-connected 1-phase to reduce the harmonic devices in the system using a modulation POD. Better control which adjusts the phase angle of the sine reference signal used for modulation of the leading phase angle of the network. To achieve power and electric power from solar panels into the virtual network. The result showed that the power system. Electric power can transmit from the solar cell into the network even more. The distortion of the harmonic series (THD) is only 1.15% and by determining the conditions for changing the light intensity instantaneously. Found that the power of the electric power and electric power, and as the value of current harmonic distortion Knicks (THD) is only 7.73%.